Keabsahan Ibadah Menggunakan Pakaian Berbahan Sutra bagi Laki-Laki dalam Tinjauan Kaidah al-Nahyu Yaqtaḍī al-Fasād: The Legality of Worship Using Silk Clothes for Men in Review of the Rules of al-Nahyu Yaqtaḍī al-Fasād - Muhammad Yusram; Abdul Munawir; Muhammad Naufal Abdilah Latif (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to explore the opinions of scholars and the review of the principle al-nahyu yaqtaḍī al-fasād regarding the validity of worship performed by men wearing silk garments. The research employs a qualitative descriptive method (non-statistical) using normative juridical and philosophical approaches. The findings are as follows. First, early scholars unanimously agreed that the use of silk by men is prohibited except in certain circumstances. There are two differing opinions regarding its impact on worship. The first opinion, held by the Hanafi and Shafi'i schools, asserts that worship performed while wearing silk is valid but sinful. The second opinion, held by the Maliki and Hanbali schools, states that such worship is invalid. Second, according to the principle of al-nahyu yaqtaḍī al-fasād, prohibitions (al-nahyu) are divided into two categories: prohibitions due to the inherent nature of the act (li ‘ainihi) and prohibitions due to external factors (li ghairihi), which are further divided into two subcategories: prohibitions due to specific attributes and prohibitions due to unrelated reasons. The use of silk by men during worship falls into the second category, specifically prohibitions due to unrelated reasons. Scholars from the Hanbali and Maliki schools argue that prohibitions in this category (prohibitions due to unrelated reasons) imply the invalidity or corruption of an act of worship. Thus, worship performed by men wearing silk garments is considered invalid. Meanwhile, according to the majority of scholars, prohibitions in this category do not imply the invalidity or corruption of an act of worship. Therefore, worship performed by men wearing silk garments is still considered valid, although sinful for using something prohibited.